FACTORS INFLUENCING SAFETY PERFORMANCE OF BUMIPUTERA SMES IN MALAYSIA - W. Nurfahizul Ifwah W. Alias; Zulkifli Mohamed; Sakinah Mat Zin; Iskandar Hasan Tan Abdullah; Rosfatihah Che Mat (International Journal of Accounting, Finance and Business, 2022)
Small and medium enterprise (SME) plays an important role in the underpinning ofa country’s economy. This study is aimed at getting a clearer view of the level of safetyperformance in various SME companies. The main concerns are the relative importance andneed of different safety management practices and how they contribute to the overall safetyperformance of Bumiputera SMEs. The results deduced represent safety rules and procedures,safety communication, and entrepreneur commitment as the most important factors influencingsafety performance. While safety promotion, worker involvement and safety training are notuseful to the prediction of safety performance. Data was quantitatively collected through closeendedquestionnaires with a sample size of 272 Bumiputera SME entrepreneurs. Data wasanalysed through correlation and multiple regression using SPSS software. This paper presentsa comprehensive diagnosis of safety performance indices of SME sector, the factors that reflectthe insignificant relationship to safety performance suggestions to improve them. This enablespractitioners and scholars to comprehend and make appropriate decisions that can enhancesafety performance among Bumiputera SME entrepreneurs in Malaysia.